An investigation of the potential and the limitations of small-scale biogas in urban Africa - Naik, Linus (Department of Chemical Engineering, 2020)
Continuing urbanisation in Sub-Saharan Africa provides many development challenges including; energy provision, waste management and sanitation. On-site biogas has the potential to provide renewable energy to meet primary energy needs, whilst also addressing waste management and possibly sanitation. In urban settings, up to 50% of the municipal waste in urban can comprise organic waste which typically remains an untapped energy source, while the total waste volume continually increases with population growth. Whilst some countries (including Ethiopia and Uganda) have support via national government and/or foreign investment for biogas deployment, their focus is on rural biogas for agricultural waste, not urban biogas for municipal waste. This thesis investigates the case for small-scale biogas as a technology to assist sustainable urban development through understanding factors which will ensure operational success to safeguard investment. The factors investigated were productivity, stability and the need for remote monitoring. The research was divided into three distinct phases which occurred chronologically. The first phase was observational and developmental, in which one biogas unit in a semi-controlled environment was monitored. Some initial insight into the factors which caused instability (in this case, the addition of simple carbohydrates) as well as two methods of mitigation of instability (namely addition of lime and a cessation of feed) were noted for future investigation. Also, in this phase, a mobile phone application, called the “Biogas Monitoring Tool” was developed and refined, accompanied by a monitoring methodology to collect information on measured variables which were considered to inform productivity and stability of small-scale biogas units. Of the variables mentioned, the laboratory method of evaluation of two in particular (pH and temperature) was replaced with more practical and rudimental measuring techniques. The appropriateness of the replacements was statistically analysed, evaluated and found to be acceptable for the intended purposes. The second phase of research involved the widespread rollout of the Biogas Monitoring Tool developed in the first phase. The platform was used to gather data from ten small-scale biogas units across southern Africa to further investigate and analyse the factors which affected the productivity and stability of smallscale biogas units. Readings of pH, burn time, pressure, mass and type of feed were captured through the Biogas Monitoring Tool over twelve months. The analysis showed episodes of instability of biogas units linked to changing feeding regimes of simple carbohydrates, organic loading rates as well as changes in feed ratios/frequency. In terms of productivity of the biogas units, seasonal fluctuations in the five units which were monitored over the winter months was evident, as well as potential underutilization of biogas produced. Furthermore, it was noted that there was better utilisation of gas for institutional installations compared to domestic installations. It was also shown that in five of the biogas units, the stability of the unit had an influence on the quality of gas produced, and it was indicative that it had an influence on the quantity of gas produced. For the third and final phase of research, theories developed from insight gleaned in second phase were tested on one biogas unit in a controlled environment. There were three sets of experiments conducted on this unit which had a pre-determined feeding regime. Also, the biogas stove was burned daily until the biogas ran out, to quantify the productivity of the biogas unit. Firstly, a stepwise addition of the organic fraction of municipal solid waste was introduced into the feeding regime. In this case, it was demonstrated that the organic fraction of municipal solid waste can in fact be the sole feed-stock for biogas unit, with the proviso that there was appropriate knowledge support which includes quick mitigation strategies for periods of instability. Secondly, the effect of pre-treatment of the organic fraction of municipal solid waste was investigated. It was found here that the pre-treatment did appear to improve the stability of the biogas unit, a consideration which may be significant for potential widespread adoption of the technology. Finally, the effect of temperature on gas production was confirmed and quantified, with higher average temperatures showing higher gas production. In conclusion, it was found that all the small-scale units which formed part of this research showed episodes of instability. When considering this technology for energy provision for urban development, there are important considerations around feedstock variability by way of feed type, volume, and frequency affect the stability of these unit. With reference to productivity, it was shown, not only that temperature naturally does affect gas production, but also that the productivity is linked to the stability. Furthermore, it was deemed that the type of setting (institutional versus domestic) was in fact more significant than the ambient temperature or the feeding regime when considering gas use and gas utilisation as indicators of productivity. Finally, with regard to knowledge support via remote monitoring, it was shown that simple and practical measurements were able to provide insight into factors which affected productivity and stability of small-scale biogas units. The final phase further utilised the remote monitoring tool to actively manage the operation of the biogas unit and quickly mitigate instability. Thus, small-scale biogas has the potential to be adopted as technology for energy provision in urban development. The limitations of the application are that waste-based biogas would meet only an portion of the total energy requirement in any particular urban area and that based on the findings of this research, all units are subject to periods of instability. There are various mitigation strategies for instability, some of which involve active management, which may be supplied remotely.